A rod-shaped binary (Zr x Hf (1-x) ) Preparation method of B2 ceramic powder

Rod-like binary (ZrxHf(1-x))B2 ceramic powder was prepared by sol-gel method, which solved the problem of mechanical properties degradation of existing ceramic materials in extreme environments, and achieved the preparation of ceramic materials with high purity and good mechanical properties, which was suitable for aerospace vehicles.

CN116730726BActive Publication Date: 2025-04-18HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310697221.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2025-04-18
Estimated Expiration
2043-06-13

AI Technical Summary

Technical Problem

Existing ultra-high temperature ceramic materials show improved oxidation resistance but deterioration in extreme environments, and it is difficult to prepare anisotropic binary (ZrxHf(1-x))B2 ceramic powders with anisotropicity through conventional reduction processes.

Method used

The gel was formed in the acetic acid system by sol-gel method. After thorough drying and grinding, it was heat treated in a high-temperature tube furnace to prepare a rod-like binary (ZrxHf(1-x)) B2 ceramic powder with adjustable length and diameter ratio.

Benefits of technology

The prepared ceramic powder has high purity and good micromorphology. It can significantly improve its mechanical properties such as impact and bending while maintaining the original thermal protection performance. It is suitable for aerospace vehicles in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004282219300000011
    Figure HDA0004282219300000011
  • Figure HDA0004282219300000021
    Figure HDA0004282219300000021
  • Figure HDA0004282219300000031
    Figure HDA0004282219300000031
Patent Text Reader

Abstract

The invention discloses a rod-shaped binary (Zr x Hf (1‑x) The preparation method of B2 ceramic powder adopts the sol-gel-carbon thermal reduction method, using boric acid, sorbitol, zirconium n-propoxide, and hafnium n-propoxide as raw materials, forming a gel in an acetic acid system and crushing it into powder, and then calcining it in a high-temperature tubular furnace to obtain the target product. The method of the present invention not only has a simple preparation process, an easy-to-control reaction process, and a short production cycle, but also the prepared rod-shaped binary (Zr x Hf (1‑x) )B2 ceramic powder has high purity and good microstructure, which can enhance the mechanical properties of the sintered body in the subsequent molding process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano material preparation, and in particular relates to a method for preparing a rod-shaped binary (Zr) nanomaterial with adjustable aspect ratio by using a sol-gel method. x Hf (1-x) )B2 preparation method of ceramic powder. Background Art

[0002] Ultra-high temperature ceramics (UHTCs) are a type of ceramic material with ultra-high melting point (greater than 3000℃), high hardness, high stability and good high temperature strength. Due to their excellent performance, ultra-high temperature ceramics have great potential application value in extreme service environments, such as the nose cone and wing leading edge of hypersonic vehicles, atmospheric reentry spacecraft and other equipment. Common ultra-high temperature ceramics include boride ceramics, carbide ceramics and nitride ceramics. Among them, boride ceramics are the hot spot of current research due to their excellent service performance.

[0003] For binary (Zr x Hf (1-x) )B2 ceramic powder, people found that the introduction of the second phase can effectively improve its antioxidant properties, but it will significantly degrade its ablation resistance and mechanical properties. According to the law of Gibbs free energy, the increase of transition metal species and the increase of formation entropy will make boride ceramics have higher thermodynamic stability and better antioxidant properties. However, due to the strong covalent bond and high formation entropy of the boride itself, the effect of hysteresis diffusion will be enhanced. Therefore, the conventional reduction process is used to prepare and synthesize anisotropic binary (Zr x Hf (1-x) )B2 ceramic powder remains a challenge.

[0004] For thermal protection materials for aerospace vehicles, in addition to high temperature resistance and oxidation resistance, they must also have high strength and good impact resistance. The poor thermal shock resistance of UHTCS seriously limits its application. To solve this problem, only by changing its composition and morphology can its overall performance be improved. The present invention forms a single boride particle into a rod-shaped grain with anisotropic morphology, which can effectively improve its toughness by activating the self-toughening mechanism. Therefore, the preparation of anisotropic rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder is an ideal choice for solving such problems. It can maintain its original good thermal protection performance while having better mechanical properties such as impact resistance and bending resistance, making it suitable for aerospace vehicles used in complex environments. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a sol-gel method for preparing a rod-shaped binary (Zr x Hf(1-x) )B2 ceramic powder method, not only the preparation process is simple, the reaction process is easy to control, the production cycle is short, but also the prepared ceramic powder has high purity and uniform microstructure, which can enhance the mechanical properties of the sintered body in the subsequent molding process.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A rod-shaped binary (Zr x Hf (1-x) )B2 A method for preparing ceramic powder, comprising the following steps:

[0008] Step A, mixing acetic acid, boric acid and sorbitol, and stirring at a constant temperature until the boric acid and sorbitol are completely dissolved in the acetic acid to obtain a mixed solution A;

[0009] Step B, mixing zirconium n-propoxide and hafnium n-propoxide, and stirring them thoroughly to obtain a mixed solution B;

[0010] Step C, stirring the mixed solution A continuously until it cools to room temperature, and then slowly and evenly dripping the mixed solution B into the mixed solution A under continuous stirring to obtain a precursor sol;

[0011] Step D, sealing the precursor sol in step C, and placing it at a constant temperature to fully gelate it to obtain a precursor gel;

[0012] Step E, fully drying the precursor gel in step D to obtain a precursor dry gel;

[0013] Step F: Grind the precursor dry gel in step E into powder, and then place it in a high-temperature tube furnace for heat treatment to obtain a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder.

[0014] Preferably, in step A, the molar ratio of boric acid to sorbitol is 1:2.

[0015] Preferably, in step A, the temperature of the constant temperature stirring is 60-90° C., and the stirring method is magnetic stirring.

[0016] Preferably, in step B, the molar ratio of the mixed zirconium n-propoxide and hafnium n-propoxide is 1-4:1-4.

[0017] Preferably, in step C, the dripping rate of the mixed solution B is 1-5 mL / min.

[0018] Preferably, in step D, the temperature of the constant temperature placement is 10-60°C.

[0019] Preferably, in step E, the drying temperature is 60-120° C. and the drying time is 8-12 h.

[0020] Preferably, in step F, grinding is performed by ball milling, the ball milling speed is 50-500 rpm, and the ball milling time is 0.5-1 h.

[0021] Preferably, in step F, the heat treatment process adopts a gradient heating method: heating from room temperature to 1000°C at a rate of 5°C / min, then heating to 1500°C at a rate of 2°C / min, heat treatment and heat preservation for 60 minutes, then cooling to 1000°C at a rate of 2°C / min, then cooling to 300°C at a rate of 5°C / min, and finally naturally cooling to room temperature.

[0022] The beneficial effects of the present invention are embodied in:

[0023] It can be seen from the technical solution provided by the present invention that the present invention adopts the sol-gel-carbothermal reduction method to prepare a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder, with boric acid, sorbitol, zirconium n-propoxide, hafnium n-propoxide as raw materials, forms gel in acetic acid system, after gelation, fully dried and crushed into powder, and then put into high temperature tube furnace for heat treatment to obtain rod-shaped binary (Zr) with adjustable aspect ratio x Hf (1-x) )B2 ceramic powder. With the increase of Hf / Zr ratio, the aspect ratio of the product gradually increases from 3.683 to 8.310, that is, the increase of Hf / Zr ratio will make the product change from short and thick to slender. Conventional boride ceramic powder is granular or flaky, and it is often toughened when used to improve its mechanical properties. x Hf (1-x) )B2 ceramic powder will be able to maintain the original thermal protection performance, and further optimize and improve its mechanical properties, including compression performance, shear performance, bending performance, torsion performance, buckling performance and impact performance. x Hf (1-x) The ultra-high temperature ceramics and their composite materials obtained by sintering B2 ceramic powder will surely highlight excellent mechanical properties such as impact resistance and bending resistance while maintaining the original good thermal protection performance; so they are suitable for aerospace vehicles used in complex environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0025] Figure 1 (1) to (7) are binary (Zr) prepared in Examples 1 to 7 of the present invention respectively. x Hf (1-x) )XRD spectrum of B2 ceramic powder for material detection.

[0026] Figure 2 (1) to (7) are binary (Zr) prepared in Examples 1 to 7 of the present invention respectively. x Hf (1-x) )B2 ceramic powder was tested for morphology at a magnification of 1k, resulting in a scanning electron microscope photograph.

[0027] Figure 3 (a) to (e) are binary (Zr) prepared in Examples 1 to 7 of the present invention, respectively. x Hf (1-x) ) EDS element distribution image of B2 ceramic powder obtained by transmission electron microscopy.

[0028] Figure 4 The binary (Zr x Hf (1-x) )B2 Image of aspect ratio change of ceramic powder. DETAILED DESCRIPTION

[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.

[0030] The following is a description of the rod-shaped binary (Zr x Hf (1-x) ) The preparation method of B2 ceramic powder is described in detail. The contents not described in detail in the embodiments of the present invention belong to the prior art known to professional and technical personnel in this field

[0031] A rod-shaped binary (Zr x Hf (1-x) )B2 A method for preparing ceramic powder, comprising the following steps:

[0032] Step A: Pour acetic acid (analytical grade) into the mixed powder of boric acid and sorbitol, and stir at a constant temperature (e.g., magnetic stirring) at 60-90° C. (most preferably 60° C.) to completely dissolve the boric acid and sorbitol in the acetic acid, thereby obtaining a clear mixed solution A.

[0033] Step B: Mix zirconium n-propoxide and hafnium n-propoxide in a certain proportion, and stir them thoroughly to obtain a mixed solution B.

[0034] Step C, stirring the mixed solution A continuously until it cools to room temperature, and then slowly dripping the mixed solution B into the mixed solution A at a rate of 1-5 mL / min under continuous stirring to obtain a precursor sol.

[0035] Step D: Seal the precursor sol prepared in step C and place it at a constant temperature of 10-60° C. (most preferably 25° C.) for 0.5-2 h (most preferably 1 h) to fully gelate the precursor sol, thereby obtaining a precursor gel.

[0036] Step E: Place the precursor gel prepared in step D in a constant temperature drying oven at 60-120° C. (most preferably 80° C.) and dry for 8-12 hours to completely dry the precursor gel to obtain a precursor dry gel.

[0037] Step F: Grind the precursor dry gel in step E into powder, and then place it in a high-temperature tube furnace for heat treatment to obtain a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder.

[0038] Specifically, a rod-shaped binary (Zr x Hf (1-x) )B2 The method of ceramic powder includes the following embodiments:

[0039] (1) In step E, the grinding into powder may be performed by ball milling the dried precursor gel, wherein the ball milling speed is preferably 250 rpm and the ball milling time is preferably 0.5 h, so that the dried precursor gel changes from a block to a powder.

[0040] (2) In step A, the molar ratio of boric acid to sorbitol is 1:2. In step B, the molar ratio of the mixed zirconium n-propoxide to hafnium n-propoxide is 1-4:1-4.

[0041] (3) In step F, the heat treatment process is carried out by using high-purity argon (Ar≥99.999%) as the protective gas and adopting a gradient heating method: heating from room temperature to 1000°C at a rate of 5°C / min, then heating to 1500°C at a rate of 2°C / min, calcining at this temperature for 60-180min, then cooling to 1000°C at a rate of 2°C / min, then cooling to 300°C at a rate of 5°C / min, and finally cooling to room temperature naturally. This high-temperature calcination allows the carbon thermal reduction reaction to proceed fully, thereby obtaining high-purity rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder.

[0042] Furthermore, the present invention provides a method for preparing a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder method has at least the following advantages:

[0043] (1) The invention provides a method for preparing a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder method to prepare rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder has high purity and can be used directly. It does not show any impurity peaks in the XRD spectrum and does not need to be further treated for impurities.

[0044] (2) The invention provides a method for preparing a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder method to prepare rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder has uniform and good microscopic morphology. The branch length of the rod-shaped ceramic powder is 4-10 microns and the average diameter is about 300-600nm.

[0045] (3) Only common laboratory equipment is required, no special equipment is required, and the process is simple and easy to operate.

[0046] (4) The invention provides a method for preparing a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder method can be mass-produced, which is very suitable for large-scale production and preparation of related ceramic materials.

[0047] In summary, the invention provides a method for preparing a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder method is not only simple in preparation process, easy to control the reaction process, short in production cycle, but also can prepare rod-shaped binary (Zr x Hf(1-x) )B2 ceramic powder has high purity and good microstructure, which can enhance the mechanical properties of the sintered body in the subsequent molding process.

[0048] In order to more clearly demonstrate the technical solution and the technical effect provided by the present invention, the following specific examples are used to illustrate the preparation of rod-shaped binary (Zr) nanostructured ... x Hf (1-x) )B2 ceramic powder method is described in detail.

[0049] Example 1

[0050] A rod-shaped binary (Zr x Hf (1-x) )B2 A method for preparing ceramic powder, comprising the following steps:

[0051] Step A: Weigh 22.26 g of boric acid and 36.43 g of sorbitol, put them into the same beaker and mix them, then pour 100 mL of acetic acid into them, and gradually heat them to 60° C. using a water bath magnetic stirrer, and stir at a constant temperature until the boric acid and sorbitol are completely dissolved in the acetic acid and the solution is completely clear, thereby obtaining a mixed solution A.

[0052] Step B: 11.06 g of hafnium n-propoxide and 1.87 g of zirconium n-propoxide (the molar ratio of the two is 4:1) are mixed and stirred thoroughly to obtain a mixed solution B.

[0053] Step C: Stir the mixed solution A continuously until it cools to room temperature, and then slowly drip the mixed solution B at a rate of 2 mL / min under continuous stirring to obtain a boride precursor sol.

[0054] Step D: Seal the precursor sol and let it stand at room temperature for 1 hour to fully gelate it, thereby obtaining a boride precursor gel.

[0055] Step E: Place the boride precursor gel in a constant temperature drying oven and dry it at 80° C. for 12 hours to completely dry it, thereby obtaining a boride precursor dry gel.

[0056] Step F: Grind the boride precursor dry gel into powder using a planetary ball mill (the ball milling speed is 250 rpm and the ball milling time is 0.5 h), then put it into a graphite crucible, put it into a high-temperature tube furnace, use high-purity argon (Ar≥99.999%) as a protective gas, heat it from room temperature to 1000°C at a rate of 5°C / min, then heat it to 1500°C at a rate of 2°C / min, heat it for 60 min, then cool it to 1000°C at a rate of 2°C / min, then cool it to 300°C at a rate of 5°C / min, and finally cool it naturally to room temperature, thereby obtaining a rod-shaped binary (Zrx Hf (1-x) )B2 ceramic powder.

[0057] Example 2

[0058] A rod-shaped binary (Zr x Hf (1-x) )B2 A method for preparing ceramic powder, comprising the following steps:

[0059] Step A: Weigh 22.26 g of boric acid and 36.43 g of sorbitol, put them into the same beaker and mix them, then pour 100 mL of acetic acid into them, and gradually heat them to 60° C. using a water bath magnetic stirrer, and stir at a constant temperature until the boric acid and sorbitol are completely dissolved in the acetic acid and the solution is completely clear, thereby obtaining a mixed solution A.

[0060] Step B: 10.37 g of hafnium n-propoxide and 2.34 g of zirconium n-propoxide (the molar ratio of the two is 3:1) are mixed and stirred thoroughly to obtain a mixed solution B.

[0061] Step C: Stir the mixed solution A continuously until it cools to room temperature, and then slowly drip the mixed solution B at a rate of 2 mL / min under continuous stirring to obtain a boride precursor sol.

[0062] Step D: Seal the precursor sol and let it stand at room temperature for 1 hour to fully gelate it, thereby obtaining a boride precursor gel.

[0063] Step E: Place the boride precursor gel in a constant temperature drying oven and dry it at 80° C. for 12 hours to completely dry it, thereby obtaining a boride precursor dry gel.

[0064] Step F: Grind the boride precursor dry gel into powder using a planetary ball mill (the ball milling speed is 250 rpm and the ball milling time is 0.5 h), then put it into a graphite crucible, put it into a high-temperature tube furnace, use high-purity argon (Ar≥99.999%) as a protective gas, heat it from room temperature to 1000°C at a rate of 5°C / min, then heat it to 1500°C at a rate of 2°C / min, heat it for 60 min, then cool it to 1000°C at a rate of 2°C / min, then cool it to 300°C at a rate of 5°C / min, and finally cool it naturally to room temperature, thereby obtaining a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder.

[0065] Example 3

[0066] A rod-shaped binary (Zr x Hf (1-x) )B2 A method for preparing ceramic powder, comprising the following steps:

[0067] Step A: Weigh 22.26 g of boric acid and 36.43 g of sorbitol, put them into the same beaker and mix them, then pour 100 mL of acetic acid into them, and gradually heat them to 60° C. using a water bath magnetic stirrer, and stir at a constant temperature until the boric acid and sorbitol are completely dissolved in the acetic acid and the solution is completely clear, thereby obtaining a mixed solution A.

[0068] Step B: 9.22 g of hafnium n-propoxide and 3.12 g of zirconium n-propoxide (the molar ratio of the two is 2:1) are mixed and stirred thoroughly to obtain a mixed solution B.

[0069] Step C: Stir the mixed solution A continuously until it cools to room temperature, and then slowly drip the mixed solution B at a rate of 2 mL / min under continuous stirring to obtain a boride precursor sol.

[0070] Step D: Seal the precursor sol and let it stand at room temperature for 1 hour to fully gelate it, thereby obtaining a boride precursor gel.

[0071] Step E: Place the boride precursor gel in a constant temperature drying oven and dry it at 80° C. for 12 hours to completely dry it, thereby obtaining a boride precursor dry gel.

[0072] Step F: Grind the boride precursor dry gel into powder using a planetary ball mill (the ball milling speed is 250 rpm and the ball milling time is 0.5 h), then put it into a graphite crucible, put it into a high-temperature tube furnace, use high-purity argon (Ar≥99.999%) as a protective gas, heat it from room temperature to 1000°C at a rate of 5°C / min, then heat it to 1500°C at a rate of 2°C / min, heat it for 60 min, then cool it to 1000°C at a rate of 2°C / min, then cool it to 300°C at a rate of 5°C / min, and finally cool it naturally to room temperature, thereby obtaining a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder.

[0073] Example 4

[0074] A rod-shaped binary (Zr x Hf (1-x) )B2 A method for preparing ceramic powder, comprising the following steps:

[0075] Step A: Weigh 22.26 g of boric acid and 36.43 g of sorbitol, put them into the same beaker and mix them, then pour 100 mL of acetic acid into them, and gradually heat them to 60° C. using a water bath magnetic stirrer, and stir at a constant temperature until the boric acid and sorbitol are completely dissolved in the acetic acid and the solution is completely clear, thereby obtaining a mixed solution A.

[0076] Step B: 6.91 g of hafnium n-propoxide and 4.68 g of zirconium n-propoxide (the molar ratio of the two is 1:1) are mixed and stirred thoroughly to obtain a mixed solution B.

[0077] Step C: Stir the mixed solution A continuously until it cools to room temperature, and then slowly drip the mixed solution B at a rate of 2 mL / min under continuous stirring to obtain a boride precursor sol.

[0078] Step D: Seal the precursor sol and let it stand at room temperature for 1 hour to fully gelate it, thereby obtaining a boride precursor gel.

[0079] Step E: Place the boride precursor gel in a constant temperature drying oven and dry it at 80° C. for 12 hours to completely dry it, thereby obtaining a boride precursor dry gel.

[0080] Step F: Grind the boride precursor dry gel into powder using a planetary ball mill (the ball milling speed is 250 rpm and the ball milling time is 0.5 h), then put it into a graphite crucible, put it into a high-temperature tube furnace, use high-purity argon (Ar≥99.999%) as a protective gas, heat it from room temperature to 1000°C at a rate of 5°C / min, then heat it to 1500°C at a rate of 2°C / min, heat it for 60 min, then cool it to 1000°C at a rate of 2°C / min, then cool it to 300°C at a rate of 5°C / min, and finally cool it naturally to room temperature, thereby obtaining a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder.

[0081] Example 5

[0082] A rod-shaped binary (Zr x Hf (1-x) )B2 A method for preparing ceramic powder, comprising the following steps:

[0083] Step A: Weigh 22.26 g of boric acid and 36.43 g of sorbitol, put them into the same beaker and mix them, then pour 100 mL of acetic acid into them, and gradually heat them to 60° C. using a water bath magnetic stirrer, and stir at a constant temperature until the boric acid and sorbitol are completely dissolved in the acetic acid and the solution is completely clear, thereby obtaining a mixed solution A.

[0084] Step B: Mix 4.61 g of hafnium n-propoxide and 6.24 g of zirconium n-propoxide (the molar ratio of the two is 1:2), and stir them thoroughly to obtain a mixed solution B.

[0085] Step C: Stir the mixed solution A continuously until it cools to room temperature, and then slowly drip the mixed solution B at a rate of 2 mL / min under continuous stirring to obtain a boride precursor sol.

[0086] Step D: Seal the precursor sol and let it stand at room temperature for 1 hour to fully gelate it, thereby obtaining a boride precursor gel.

[0087] Step E: Place the boride precursor gel in a constant temperature drying oven and dry it at 80° C. for 12 hours to completely dry it, thereby obtaining a boride precursor dry gel.

[0088] Step F: Grind the boride precursor dry gel into powder using a planetary ball mill (the ball milling speed is 250 rpm and the ball milling time is 0.5 h), then put it into a graphite crucible, put it into a high-temperature tube furnace, use high-purity argon (Ar≥99.999%) as a protective gas, heat it from room temperature to 1000°C at a rate of 5°C / min, then heat it to 1500°C at a rate of 2°C / min, heat it for 60 min, then cool it to 1000°C at a rate of 2°C / min, then cool it to 300°C at a rate of 5°C / min, and finally cool it naturally to room temperature, thereby obtaining a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder.

[0089] Example 6

[0090] A rod-shaped binary (Zr x Hf (1-x) )B2 The method for preparing ceramic powder may include the following steps:

[0091] Step A: Weigh 22.26 g of boric acid and 36.43 g of sorbitol, put them into the same beaker and mix them, then pour 100 mL of acetic acid into them, and gradually heat them to 60° C. using a water bath magnetic stirrer, and stir at a constant temperature until the boric acid and sorbitol are completely dissolved in the acetic acid and the solution is completely clear, thereby obtaining a mixed solution A.

[0092] Step B: 3.46 g of hafnium n-propoxide and 7.02 g of zirconium n-propoxide (the molar ratio of the two is 1:3) are mixed and stirred thoroughly to obtain a mixed solution B.

[0093] Step C: Stir the mixed solution A continuously until it cools to room temperature, and then slowly drip the mixed solution B at a rate of 2 mL / min under continuous stirring to obtain a boride precursor sol.

[0094] Step D: Seal the precursor sol and let it stand at room temperature for 1 hour to fully gelate it, thereby obtaining a boride precursor gel.

[0095] Step E: Place the boride precursor gel in a constant temperature drying oven and dry it at 80° C. for 12 hours to completely dry it, thereby obtaining a boride precursor dry gel.

[0096] Step F: Grind the boride precursor dry gel into powder using a planetary ball mill (the ball milling speed is 250 rpm and the ball milling time is 0.5 h), then put it into a graphite crucible, put it into a high-temperature tube furnace, use high-purity argon (Ar≥99.999%) as a protective gas, heat it from room temperature to 1000°C at a rate of 5°C / min, then heat it to 1500°C at a rate of 2°C / min, heat it for 60 min, then cool it to 1000°C at a rate of 2°C / min, then cool it to 300°C at a rate of 5°C / min, and finally cool it naturally to room temperature, thereby obtaining a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder.

[0097] Example 7

[0098] A rod-shaped binary (Zr x Hf (1-x) )B2 A method for preparing ceramic powder, comprising the following steps:

[0099] Step A: Weigh 22.26 g of boric acid and 36.43 g of sorbitol, put them into the same beaker and mix them, then pour 100 mL of acetic acid into them, and gradually heat them to 60° C. using a water bath magnetic stirrer, and stir at a constant temperature until the boric acid and sorbitol are completely dissolved in the acetic acid and the solution is completely clear, thereby obtaining a mixed solution A.

[0100] Step B: 2.77 g of hafnium n-propoxide and 7.49 g of zirconium n-propoxide (the molar ratio of the two is 1:4) are mixed and stirred thoroughly to obtain a mixed solution B.

[0101] Step C: Stir the mixed solution A continuously until it cools to room temperature, and then slowly drip the mixed solution B at a rate of 2 mL / min under continuous stirring to obtain a boride precursor sol.

[0102] Step D: Seal the precursor sol and let it stand at room temperature for 1 hour to fully gelate it, thereby obtaining a boride precursor gel.

[0103] Step E: Place the boride precursor gel in a constant temperature drying oven and dry it at 80° C. for 12 hours to completely dry it, thereby obtaining a boride precursor dry gel.

[0104] Step F: Grind the boride precursor dry gel into powder using a planetary ball mill (the ball milling speed is 250 rpm and the ball milling time is 0.5 h), then put it into a graphite crucible, put it into a high-temperature tube furnace, use high-purity argon (Ar≥99.999%) as a protective gas, heat it from room temperature to 1000°C at a rate of 5°C / min, then heat it to 1500°C at a rate of 2°C / min, heat it for 60 min, then cool it to 1000°C at a rate of 2°C / min, then cool it to 300°C at a rate of 5°C / min, and finally cool it naturally to room temperature, thereby obtaining a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder.

[0105] The (Zr x Hf (1-x) )B2 ceramic powder was tested for purity and morphology, and the following results were obtained:

[0106] (1) The rod-shaped binary (Zr) prepared in Examples 1 to 7 of the present invention were analyzed by X-ray diffraction analyzer. x Hf (1-x) )B2 ceramic powder was tested for material, and the XRD spectra were as follows Figure 1 As shown in (1)-(7), it can be seen that the rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powders all show high purity in XRD patterns without any impurity peaks.

[0107] (2) The rod-shaped binary (Zr) prepared in Examples 1 to 7 of the present invention were respectively observed by scanning electron microscopy. x Hf (1-x) )B2 ceramic powder is tested for morphology, and the following is obtained: Figure 2 From the scanning electron microscope photos shown in (1)-(7), we can see that: x Hf (1-x) )B2 ceramic powder has a multi-branch structure, with several to a dozen branches, each branch is several microns long, and the average diameter is about 0.5-1μm. x Hf (1-x) )B2 ceramic powder aspect ratio is 8.310; the rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder aspect ratio is 7.588; the rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder aspect ratio is 6.637; the rod-shaped binary (Zr xHf (1-x) )B2 ceramic powder aspect ratio is 5.635; the rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder aspect ratio is 4.785; the rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder aspect ratio is 3.901; the rod-shaped binary (Zr x Hf (1-x) ) The aspect ratio of the B2 ceramic powder is 3.683. The aspect ratio of Example 1 of the present invention is the largest.

[0108] (3) The rod-shaped binary (Zr) prepared in Example 4 of the present invention was observed by transmission electron microscopy. x Hf (1-x) )B2 ceramic powder was characterized to obtain Figure 3 As shown in the picture, the element distribution EDS image shows that the Zr and Hf elements are evenly distributed.

[0109] (4) Figure 4 The image of the change in the aspect ratio of the product when Hf:Zr gradually changes from 4:1 to 1:4 shows that as the Hf:Zr ratio decreases, the product morphology gradually changes from slender to short and thick, and the aspect ratio gradually decreases.

[0110] The results show that by adjusting the sol formula and preparation process, the present invention can prepare high-purity, uniform-shaped rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder. The embodiment of the present invention not only has a simple preparation process, does not involve a complex reaction process, and can be prepared in a short period of time, but also the prepared rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder has high purity and good micromorphology, which can provide a technical basis and commercial potential for large-scale synthesis of ultra-high temperature ceramic material structural toughening.

[0111] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A rod-shaped binary (Zr x Hf (1-x) )B2 A method for preparing ceramic powder, characterized in that: The following steps are involved: Step A, mixing acetic acid, boric acid and sorbitol, and stirring at a constant temperature until the boric acid and sorbitol are completely dissolved in the acetic acid to obtain a mixed solution A, wherein the molar ratio of boric acid to sorbitol is 1:2; Step B, mixing zirconium n-propoxide and hafnium n-propoxide, and stirring them thoroughly to obtain a mixed solution B, wherein the molar ratio of the mixed zirconium n-propoxide and hafnium n-propoxide is 1-4:1-4; Step C, stirring the mixed solution A continuously until it cools to room temperature, and then slowly and evenly dripping the mixed solution B into the mixed solution A under continuous stirring to obtain a precursor sol; Step D, sealing the precursor sol in step C, and placing it at a constant temperature to fully gelate it to obtain a precursor gel; Step E, fully drying the precursor gel in step D to obtain a precursor dry gel; Step F: Grind the precursor dry gel in step E into powder by ball milling at a speed of 50-500 rpm and a time of 0.5-1 h, and then place the powder in a high temperature tube furnace for heat treatment to obtain a rod-shaped binary (Zr x Hf (1-x) )B2 ceramic powder, wherein the heat treatment process adopts a gradient heating method: heating from room temperature to 1000°C at a rate of 5°C / min, then heating to 1500°C at a rate of 2°C / min, heat treating at the temperature for 60 minutes, then cooling to 1000°C at a rate of 2°C / min, then cooling to 300°C at a rate of 5°C / min, and finally naturally cooling to room temperature.

2. A rod-shaped binary (Zr) with adjustable aspect ratio as claimed in claim 1 x Hf (1-x) )B2 A method for preparing ceramic powder, characterized in that: In step A, the temperature of the constant temperature stirring is 60-90° C., and the stirring method is magnetic stirring.

3. A rod-shaped binary (Zr) with adjustable aspect ratio as claimed in claim 1 x Hf (1-x) )B2 A method for preparing ceramic powder, characterized in that: In step C, the dripping rate of the mixed solution B is 1-5 mL / min.

4. A rod-shaped binary (Zr) with adjustable aspect ratio as claimed in claim 1 x Hf (1-x) )B2 A method for preparing ceramic powder, characterized in that: In step D, the temperature of the constant temperature placement is 10-60°C.

5. A rod-shaped binary (Zr) with adjustable aspect ratio as claimed in claim 1 x Hf (1-x) )B2 A method for preparing ceramic powder, characterized in that: In step E, the drying temperature is 60-120° C. and the drying time is 8-12 h.

6. A rod-shaped binary (Zr) with adjustable aspect ratio obtained by the preparation method according to any one of claims 1 to 5 x Hf (1-x) )B2 ceramic powder.

Citation Information

Patent Citations

  • Preparation method and application of boride ceramic precursor

    CN104086180A

  • Method for preparing ZrB2 powder

    CN106631033A